Clopidogrel as a donor probe and thioenol derivatives as flexible promoieties for enabling H2S biomedicine - Yaoqiu Zhu (Nature Portfolio, 2018)
Hydrogen sulphide (H2S) is a gaseous signalling molecule, which has shown therapeutic value. Here, the authors show that a thioenol metabolite of the antithrombotic drug clopidogrel is an efficient H2S donor and masked thioenols can be linked to existing compounds to develop H2S-releasing agents.